Recent Advances in Exploration and Biotechnological Production of Bioactive Compounds in Three Cyanobacterial Genera: Nostoc, Lyngbya, and Microcystis - Thuan, Nguyen Huy; An, Tran Tuan; Shrestha, Anil; Canh, Nguyen Xuan; Sohng, Jae Kyung; Dhakal, Dipesh (Frontiers in Chemistry, 2019)
Cyanobacteria, are only Gram-negative bacteria with the capacity of oxygenic photosynthesis, so termed as “Cyanophyta” or “blue-green algae.” Their habitat is ubiquitous, which includes the diverse environments, such as soil, water, rock and other organisms (symbiosis, commensalism, or parasitism, etc.,). They are characterized as prominent producers of numerous types of important compounds with anti-microbial, anti-viral, anti-inflammatory and anti-tumor properties. Among the various cyanobacterial genera, members belonging to genera Nostoc, Lyngbya, and Microcystis possess greater attention. The major reason for that is the strains belonging to these genera produce the compounds with diverse activities/structures, including compounds in preclinical and/or clinical trials (cryptophycin and curacin), or the compounds retaining unique activities such as protease inhibitor (micropeptins and aeruginosins). Most of these compounds were tested for their efficacy and mechanism of action(MOA) through in vitro and/or in vivo studies. Recently, the advances in culture techniques of these cyanobacteria, and isolation, purification, and chromatographic analysis of their compounds have revealed insurmountable novel bioactive compounds from these cyanobacteria. This review provides comprehensive update on the origin, isolation and purification methods, chemical structures and biological activities of the major compounds from Nostoc, Lyngbya, and Microcystis. In addition, multi-omics approaches and biotechnological production of compounds from selected cyanobacterial genera have been discussed.